Stig Sjödin's poetry in Swedish journals: A bibliography - Nilsson, Magnus (Malmö University, 2020)
Bibliography of Stig Sjödin's poetry in Swedish journals. The compilation is based on Professor Lars Furuland's bibliography in Svenskt bibliografiskt lexikon and on his own searches.

The dataset was originally published in DiVA and moved to SND in 2024.

Bibliografi över Stig Sjödins lyrik i svenska tidskrifter. Sammanställningen bygger på professor Lars Furulands bibliografi i Svenskt bibliografiskt lexikon samt på egna sökningar.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Stig Sjödins lyrik i svenska tidskrifter: En bibliografi
Keywords: literary research; litteraturvetenskap; bibliographies (catalogues and directories); bibliografier; personal bibliographies; personbibliografier; lyric poetry; lyrik; General Literary studies; Litteraturvetenskap